Trend of Applying the Conceptual Change Model in Physics Learning: Systematic Literature Review - Wati, Erma; Samsudin, Achmad; Saepuzaman, Duden; Sozbilir, Mustafa (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Physics learning often faces challenges in improving students' conceptual understanding. Conceptual change models are widely used to address this. This study aims to analyze these gaps, review the materials used, and identify improvements made. The study examined fifty-seven articles from four good-quality journal databases: Scopus, Science Direct, Eric, and Sage Journal. This study uses a systematic literature review method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) technique. The analyzed data was visualized based on selected articles in the form of mapping tabula, including the country of origin of the research, the physics content studied, the frequency of topic material, and the focus of the problem in the research over the last five years (2019-2024). The findings show that the trend of applying learning models in various physics learning materials over the past five years has varied, with ten countries implementing conceptual change model research. The content of matter has varied, including complete kinematics, fluids, pendulums, temperature and heat, sound waves, light waves, Pascal's laws, and quantum. The benefits of integrating conceptual change models in physics learning include diagnosing students who experience misunderstandings and improving conceptual understanding. One of the next research recommendations is to apply momentum and impulse materials while still using a conceptual change model in physics learning.